Surviving Change. On the Metamorphoses of Theatre Criticism. Duška Radosavljević (Ed.) “Theatre Criticism. Changing Landscapes”, London: Bloomsbury, 2016 - PEDESTRU, Emma Alexandra (Studia Universitatis Babeș-Bolyai Dramatica, 2017)
Nowadays, when thinking about the practice of theatre criticism, one tends to unknowingly equate it with the ownership of an inherited title, like that of a crown prince in a newly proclaimed republic. Both the unfortunate former future monarch and the critic hold a certain distinction, seeming unapproachable by the commoners, but not quite finding their place in the modern world. A regular theatregoer finds it just as hard to clearly define the role of the professional reviewer as any republican would to yield to the authority of a crownless king. Thus, is a shift of paradigm likely to occur? Can theatre criticism adjust to the ever-changing landscapes of theatre and, even more importantly, journalism? As it happens, the change is already taking place, right before our eyes, and it already constitutes a full-blown phenomenon, thoroughly examined in a comprehensive new book edited by Duška Radosavljević: Theatre Criticism. Changing Landscapes, published by Bloomsbury in 2016.